A cluster randomised trial of a school-based resilience intervention to decrease tobacco, alcohol and illicit drug use in secondary school students: study protocol - Hodder Rebecca K; Freund Megan; Bowman Jenny; Wolfenden Luke; Campbell Elizabeth; Wye Paula; Hazell Trevor; Gillham Karen; Wiggers John (BMC, 2012)
Abstract Background Whilst schools provide a potentially appropriate setting for preventing substance use among young people, systematic review evidence suggests that past interventions in this setting have demonstrated limited effectiveness in preventing tobacco, alcohol and other drug use. Interventions that adopt a mental wellbeing approach to prevent substance use offer considerable promise and resilience theory provides one method to impact on adolescent mental well-being. The aim of the proposed study is to examine the efficacy of a resilience intervention in decreasing the tobacco, alcohol and illicit drug use of adolescents. Methods A cluster randomised controlled trial with schools as the unit of randomisation will be undertaken. Thirty two schools in disadvantaged areas will be allocated to either an intervention or a control group. A comprehensive resilience intervention will be implemented, inclusive of explicit program adoption strategies. Baseline surveys will be conducted with students in Grade 7 in both groups and again three years later when the student cohort is in Grade 10. The primary outcome measures will include self-reported tobacco, alcohol, marijuana and other illicit drug use. Comparisons will be made post-test between Grade 10 students in intervention and control schools to determine intervention effectiveness across all measures. Discussion To the authors' knowledge this is the first randomised controlled trial to evaluate the effectiveness of a comprehensive school-based resilience intervention, inclusive of explicit adoption strategies, in decreasing tobacco, alcohol and illicit drug use of adolescents attending disadvantaged secondary schools. Trial registration ACTRN12611000606987